Key Performance Indicators of Chest Pain Management in Emergency Department; a Letter to the Editor - Taghizadeh, Mehrdad; Taghipour, Roghayeh; Heydari, Kamran (Archives of Academic Emergency Medicine, 2018)
Chest pain is a common complaint among those presenting to emergency department (ED) and is associated with a high rate of mortality. Based on National Center for Health Statistics, chest pain leads to about 6 million visits to EDs in United State. In Iran, ischemic cardiac diseases are the second cause of death in people aged 15 to 49 years. While less than 10% of the patients presenting to ED with chest pain are affected with myocardial infarction (MI), 33% of MI cases are silent. Timely diagnosis and revascularization of ischemic part, using thrombolytic agents or percutaneous coronary intervention (PCI), can save cardiac function and the patient’s life. Therefore, in this regard the emphasis is on rapid referral of the patients to treatment centers, initiation of diagnostic measures such as electrocardiography (ECG) and in case of meeting the required criteria, transfer to cat lab for PCI. American Heart Association (AHA) has introduced the proper door to ECG time as 10 minutes if it has not been done in the ambulance. Based on this recommendation, AHA has defined the aims of coronary reperfusion as prescription of thrombolytic in the initial 30 minutes after admission of the patient to ED or PCI in the initial 90 minutes after admission to ED.